Progress Towards a Far-Infrared Spatial/Spectral Interferometry Laboratory Testbed Instrument - Locke D. Spencer; Chris S. Benson; Jeremy P. Scott; Geoffrey R. H. Sitwell; Adam Sundberg; Vince F. Weiler; David A. Naylor (Light, Energy and the Environment 2018 (E2, FTS, HISE, SOLAR, SSL), 2018)
Characterization results are presented for a double-Fourier spatial/spectral laboratory interferometer. This instrument is a testbed platform for developing imaging techniques, data processing algorithms, and component characterization for space-based astronomical applications in the far-infrared.
Keywords: Fourier transform spectroscopy; Fourier transforms; Image reconstruction; Imaging techniques; Spatial resolution; Spectral imaging